Does Informal Labor Affect Food Security? Evidence from Indonesia - Rizki Tri Anggara; Elsya Gumayanti Alfahma (Universitas Negeri Semarang, 2024)
This study analyzes the impact of informal employment on household food security in Indonesia, focusing on concern about food sufficiency, access to nutritious food, and reduced food intake. Using data from the March 2021 Indonesia National Socioeconomic Survey, binary logistic regression models were applied to a weighted sample of household heads actively employed in formal and informal sectors. The analysis reveals that informal employment significantly undermines food security across all measures, with informally employed households facing higher risks of food shortages, reduced nutritional access, and inadequate intake. Vulnerabilities are more pronounced in rural and non-agricultural households. Protective factors such as education, internet access, and health insurance enhance food security, while larger household sizes and underemployment exacerbate risks. This study emphasizes the urgent need for targeted interventions to safeguard food security for vulnerable populations in Indonesia.